De Reis om de Wereld - Darwin, Charles, 1809-1882; Brandt, J. (Salt Lake City, UT : Project Gutenberg, 2010)
"De Reis om de Wereld" by Charles Darwin is a travel memoir and scientific journal originally published in 1839. The book chronicles Darwin's nearly five-year voyage aboard HMS Beagle, documenting his observations across South America and beyond. Through vivid descriptions of geology, biology, and anthropology, Darwin records the explorations that would shape his groundbreaking theories. Written from detailed field notes and personal diary entries, this account captures a young naturalist's keen observations during an era of global discovery and scientific revolution. (This is an automatically generated summary.)
Translation of: Voyage of the Beagle
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Voyage_of_the_Beagle
Release date is 2010-09-19
Jeroen Hellingman and the Online Distributed Proofreading Team
Keywords: Natural history; Beagle Expedition (1831-1836); Geology; Voyages around the world -- History -- 19th century; South America -- Discovery and exploration